Status of installation and commissioning for the Belle II time-of-propagation counter. (2nd August 2017) - Maeda, Y.
Abstract: The Time-Of-Propagation (TOP) counter is a novel device for particle identification for the barrel region of the Belle II experiment, where, information of Cherenkov light propagation time is used to reconstruct its ring image. We successfully finished the detector production and installation to the Belle II structure in 2016. Commissioning of the installed detector has been on going, where the detector operation in the 1.5-T magnetic field was studied. Although we found a problem where photomultipliers were mechanically moved due to the magnetic force, it was immediately fixed. Performance was evaluated with cosmic ray data, the number of photon hits was confirmed to be consistent with simulation within 15–30%.